Post-exercise rehydration: Comparing the efficacy of three commercial oral rehydration solutions - Peden, Donald L.; Funnell, Mark P.; Reynolds, Kirsty M.; Kenefick, Robert W.; Cheuvront, Samuel N.; Mears, Stephen A.; James, Lewis J. (Frontiers in Sports and Active Living, 2023)
Introduction This study compared the efficacy of three commercial oral rehydration solutions (ORS) for restoring fluid and electrolyte balance, after exercise-induced dehydration. Method Healthy, active participants (N = 20; ♀ = 3; age ∼27 y, V˙O2peak ∼52 ml/kg/min) completed three randomised, counterbalanced trials whereby intermittent exercise in the heat (∼36°C, ∼50% humidity) induced ∼2.5% dehydration. Subsequently, participants rehydrated (125% fluid loss in four equal aliquots at 0, 1, 2, 3 h) with a glucose-based (G-ORS), sugar-free (Z-ORS) or amino acid-based sugar-free (AA-ORS) ORS of varying electrolyte composition. Urine output was measured hourly and capillary blood samples collected pre-exercise, 0, 2 and 5 h post-exercise. Sodium, potassium, and chloride concentrations in urine, sweat, and blood were determined. Results Net fluid balance peaked at 4 h and was greater in AA-ORS (141 ± 155 ml) and G-ORS (101 ± 195 ml) than Z-ORS (−47 ± 208 ml; P ≤ 0.010). Only AA-ORS achieved positive sodium and chloride balance post-exercise, which were greater for AA-ORS than G-ORS and Z-ORS (P ≤ 0.006), as well as for G-ORS than Z-ORS (P ≤ 0.007) from 1 to 5 h. Conclusion when provided in a volume equivalent to 125% of exercise-induced fluid loss, AA-ORS produced comparable/superior fluid balance and superior sodium/chloride balance responses to popular glucose-based and sugar-free ORS.